2014
DOI: 10.1007/s10803-014-2280-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Literature Review of Comprehension Strategies in Core Content Areas for Students with Autism Spectrum Disorder

Abstract: Understanding text can increase access to educational, vocational, and recreational activities for individuals with autism spectrum disorder (ASD); however, limited research has been conducted investigating instructional practices to remediate or compensate for these comprehension challenges. The current comprehensive literature review expanded previous reviews and evaluated research quality using Reichow (Evidence-based practices and treatments for children with autism, pp 25-39. doi: 10.1007/978-1-4419-6975-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 54 publications
2
40
0
1
Order By: Relevance
“…Evidence‐based practices are those research‐based practices meeting rigorous criteria, which when studied, consistently produce meaningful outcomes for participants (Torres, Farley, & Cook, ). At present, few instructional practices specific to reading comprehension and ASD have been identified as evidence based (Knight & Sartini, ). However, relevant reviews have identified a number of effective practices (Accardo, ; El Zein, Solis, Vaughn, & McCulley, ; Finnegan & Mazin, ).…”
Section: Self‐efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence‐based practices are those research‐based practices meeting rigorous criteria, which when studied, consistently produce meaningful outcomes for participants (Torres, Farley, & Cook, ). At present, few instructional practices specific to reading comprehension and ASD have been identified as evidence based (Knight & Sartini, ). However, relevant reviews have identified a number of effective practices (Accardo, ; El Zein, Solis, Vaughn, & McCulley, ; Finnegan & Mazin, ).…”
Section: Self‐efficacymentioning
confidence: 99%
“…Identified effective practices include anaphoric cueing (Solis, McCulley, & Zein, 2013), compare and contrast diagrams (Carnahan & Williamson, 2013), cooperative learning (Kamps, Barbetta, Leonard, & Delquadri, 1994;Kamps, Leonard, Potucek, & Garrison-Harrell, 1995;Whalon & Hanline, 2008), direct/explicit instruction (Flores & Ganz, 2007;Flores & Ganz, 2009;Roux, Dion, Barrette, Dupere, & Fuchs, 2014), graphic organizers (Carnahan & Williamson, 2013), question generation (Hua et al, 2012), read-alouds (Mims, Hudson, & Browder, 2012), reciprocal questioning (Whalon & Hanline, 2008), story structure maps/character event maps (Stringfield, Luscre, & Gast, 2011;Williamson, Carnahan, Birri, & Swoboda, 2014), and systematic prompts (Mims et al, 2012). Of the instructional practices, only systematic prompts and visual supports, for example, graphic organizers and diagrams, have been identified as evidence based (Knight & Sartini, 2015).…”
mentioning
confidence: 99%
“…Two researchers rated independently the methodological rigor of each selected study using the guidelines prescribed in the Evaluative Method for Determining Evidence-Based Practices in Autism (Reichow, Volkmar, & Cicchetti, 2008). These guidelines can assess the study quality of group and single subject research with reliable and valid assessment results (Knight & Sartini, 2015;Watkins et al, 2015).…”
Section: Data Extraction and Assessment Of Study Qualitymentioning
confidence: 99%
“…The use of technology to teach several academic and social skills to students with ASD has a long history, since the first study reporting the use of a computer to increase understanding of how letters and sounds form words, and how texts can form expressions (37, 38). However, very few studies have explored or tested the use of assistive technology to facilitate reading comprehension among ASD subjects (39).…”
Section: Introductionmentioning
confidence: 99%